Research and theological teaching - Didaskalia, Didaskalia (2004)
Theology, as a scientific discipline, produces knowledge before a specific and real world. So research is one of priorizing activities to promote the dialogue with other disciplines and to propose concrete solutions to social problems. In such a dialogue theologians must bear the particular foundation, pertinence and rigor of their discourse. This article attempts to show how research feeds theology teaching at Javeriana University Theology Department.